Simultaneous Detection of Methicillin-Resistant Staphylococcus aureus, Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa by Multiplex PCR - Thong, Kwai Lin; Lai, M.Y.; Teh, Cindy Shuan Ju; Chua, Kek Heng (Malaysian Society of Parasitology and Tropical Medicine, 2011)
A PCR-based assay that can simultaneously detect and differentiate five different types of nosocomial bacterial pathogens was developed. Six pairs of selected primers targeting femA (132 bp) and mecA (310 bp) of methicillin-resistant Staphylococcus aureus, gltA (722 bp) of Acinetobacter baumannii, phoA (903 bp) of Escherichia coli, mdh (364 bp) of Klebsiella pneumoniae and oprL (504 bp) of Pseudomonas aeruginosa were used in this study. The conditions were optimized for the multiplex PCR to ensure specific amplification of the selected targets. Sensitivity and specificity tests were also carried out using a blind test approach on 50 bacterial cultures and resulted in 100 for both positive and negative predictive values.